Studi Waveform Retracking Jason-2 di Pesisir Barat Daya Sumatera - Nadzir, Zulfikar Adlan; Hasan, Muhammad Akmal (Jurnal Kelautan Tropis, 2025)
Monitoring sea level changes in coastal areas is critical to understand ocean dynamics and their impact on the environment and human activities. Satellite altimetry has been the main tool in these studies, but its use in coastal areas still faces obstacles, especially due to variations in waveforms reflected from the sea surface. This study evaluates the accuracy of several altimetry waveform retracking methods (OCOG, Threshold 10%, and Threshold 30% ) on the southwest coast of Sumatra. The analysis was conducted using Jason-2 data on two passes, namely pass 077 and pass 153, with validation against two tide gauge stations nearby. Results showed that the Threshold 30% method provided a more accurate estimation of the Leading Edge Point (LEP) position than the other methods, with an average difference of only 0.1 gates (0.32%) from the reference value. Meanwhile, the OCOG method has the worst performance with a difference of 6.27 gates (20.22%), indicating its inability to handle coastal waveform variations on the location. Validation of the tide gauge data shows that retracking with a 10% Threshold improves the precision of Sea Surface Height (SSH) data with the highest IMP improvement value of 65.2% and the smallest standard deviation on the Threshold 30%. This finding confirms that choosing the right retracking method plays a crucial role in improving the accuracy of satellite altimetry in coastal areas. Therefore, the Threshold method is recommended for further analysis to improve the quality of altimetry data in coastal Indonesia.   Pemantauan perubahan muka air laut di wilayah pesisir sangat penting untuk memahami dinamika laut dan dampaknya terhadap lingkungan serta aktivitas manusia. Satelit Altimetri telah menjadi alat utama dalam studi ini, tetapi penggunaannya di wilayah pesisir masih menghadapi tantangan, terutama akibat variasi bentuk waveform yang dipantulkan dari permukaan laut. Studi ini mengevaluasi keakuratan metode waveform retracking altimetri OCOG, Threshold 10%, dan Threshold 30% di pesisir barat daya Sumatra. Analisis dilakukan menggunakan data Jason-2 pada dua jalur lintasan, yaitu pass 077 dan pass 153, dengan validasi terhadap data pasang surut. Hasil penelitian menunjukkan bahwa metode Threshold 30% memberikan estimasi posisi Leading Edge Point (LEP) yang lebih akurat dibandingkan metode lainnya, dengan selisih rata-rata hanya 0,1 gate (0,32%) dari nilai referensi. Sementara itu, metode OCOG memiliki performa paling tidak akurat dengan selisih sebesar 6,27 gate (20,22%), yang mengindikasikan ketidakmampuannya dalam menangani variasi waveform di pesisir. Validasi terhadap data pasang surut menunjukkan bahwa retracking dengan Threshold 10% meningkatkan presisi data Sea Surface Height (SSH) dengan nilai peningkatan IMP tertinggi sebesar 65,2% dan standar deviasi terkecil pada metode Threshold 30%. Temuan ini menegaskan bahwa pemilihan metode retracking yang tepat berperan krusial dalam meningkatkan akurasi satelit altimetri di wilayah pesisir. Oleh karena itu, metode Threshold direkomendasikan untuk analisis lebih lanjut guna meningkatkan kualitas data altimetri di kawasan pesisir Indonesia.